STRATEGI PENINGKATAN SANITASI ROOM ATTENDANT UNTUK MENCIPTAKAN CITRA POSITIF PADA SAHID BATAM CENTER HOTEL & CONVENTION - Fakhri, Nurul; Supardi; Lubis, Arina Luthfini (Puslitabmas Batam Tourism Polytecnic, 2023)
Sanitation, which encompasses the maintenance of both personal and environmental cleanliness, serves as a pivotal measure in preventing the spread of diseases, particularly in communal settings such as the Sahid Batam Center Hotel & Convention. Within the context of this establishment, the focus of this study lies in investigating the sanitation management strategies employed by room attendants to bolster the hotel's favorable perception. Employing qualitative methodologies, the research involved in-depth interviews with key personnel from the housekeeping department, including the executive housekeeper, housekeeping supervisor, and room attendant, alongside soliciting feedback from a guest. The findings underscore the meticulous adherence to sanitation protocols and cleanliness standards as outlined in the Standard Operating Procedures (SOP). It becomes apparent that such stringent adherence not only mitigates the occurrence of undesirable incidents but also fosters an environment conducive to promoting positive perceptions of the Sahid Batam Center Hotel & Convention. Notably, guests' responses affirm the efficacy of these efforts, citing the establishment's commendable hygiene standards and the exemplary warmth exhibited by its staff towards patrons. This confluence of factors underscores the hotel's commitment to not only maintaining optimal cleanliness but also cultivating a hospitable ambiance that enhances its overall image.